LPPM FINANCIAL APPLICATION STMIK BASED DESKTOP AND MYSQL SERVER - Bambang Ari Wibowo; Muhamad Muslihudin; Siti Mukodimah (Jurnal TAM (Technology Acceptance Model), 2020)
Application is a supporting component that can be used to help daily student needs such as data processing, image processing, number processing, and others. In an effort to improve the service of the Ministry of Research and Community Services Institute of High School Management Informatics and computer PRINGSEWU develop Financial action Payment Journal High School Informatics Management and Pringsewu computer. The application was developed with a waterfall model and designed with the concept of a well-sealed model with the stage of the development of the context diagram and lowered to the Data Flow diagram. The application was developed using the desktop model using the Delphi programming language and combined to a server system and MySQL database. Results of the study and the implentation of the financial application system of the Institute of Research and community service of high school informatics management and computer PRINGSEWU all applications are well integrated and the application system is running as it is recorded The journal payment data and the data of the registered student can be accommodated quickly and precisely.